FACTORS AFFECTING AVIATION SECURITY PERFORMANCE AT MUARA BUNGO AIRPORT - Sony Aditya Pratama; Baihaqi Baihaqi; Yumiati Yumiati (SEAN Institute, 2023)
This studi explores the factors influencing employee performance at Muara bungo airport, focusing on discipline, work motivation, and competence. The research findings reveal that employee discipline positively impacts performance, emphasizing the importance of punctuality, adherence to procedures, and responsibility in achieving organizational goals. Additionally, the study highlights the significance of work motivation in driving employee performance, emphasizing the role of fair compensation, recognition, and developmental opportunities. Furthermore, competence emerges as a key factor, with skilled and knowledgeable employees exhibiting higher performance levels. The research suggests strategies such as strengthening discipline, enhancing work motivation, and focusing on competence development to optimize employee performance. The studi also recommends fostering a culture of safety and security, improving communication and collaboration, implementing performance evaluation and feedback mechanisms, and continuously monitoring and adapting approaches. By implementing these suggestions, Muara bungo airport can effectively enhance employee performance, contributing to the organization's success and ensuring a safer and more efficient aviation environment